2014
DOI: 10.1103/physrevd.89.103515
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale structure formation with massive neutrinos and dynamical dark energy

Abstract: Over the next decade, cosmological measurements of the large-scale structure of the Universe will be sensitive to the combined effects of dynamical dark energy and massive neutrinos. The matter power spectrum is a key repository of this information. We extend higher-order perturbative methods for computing the power spectrum to investigate these effects over quasi-linear scales. Through comparison with N-body simulations we establish the regime of validity of a Time-Renormalization Group (Time-RG) perturbative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
85
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(96 citation statements)
references
References 81 publications
(128 reference statements)
11
85
0
Order By: Relevance
“…We follow the approach discussed in detail in Heitmann et al (2015), applying a small correction to account for the scale dependence of the growth function as discussed in Upadhye et al (2014). We provide a short summary of our neutrino treatment here and show comparisons to results found by other groups in Section 4.…”
Section: Treatment Of Neutrinosmentioning
confidence: 99%
See 4 more Smart Citations
“…We follow the approach discussed in detail in Heitmann et al (2015), applying a small correction to account for the scale dependence of the growth function as discussed in Upadhye et al (2014). We provide a short summary of our neutrino treatment here and show comparisons to results found by other groups in Section 4.…”
Section: Treatment Of Neutrinosmentioning
confidence: 99%
“…Meanwhile, at higher redshifts z 1, our use of the scale-independent CDM + baryon growth factor leads to an error at large scales where neutrinos cannot be neglected. Fortunately, these scales are linear, and Upadhye et al (2014) showed that the resulting error can be removed by multiplying the N-body power spectrum by the k-…”
Section: Treatment Of Neutrinosmentioning
confidence: 99%
See 3 more Smart Citations